Acceptability and effects of the raga music listening intervention for blood pressure: a pilot study among the Indian ethnic population in Malaysia (Indian Journal of Traditional Knowledge (IJTK), 2025)
This study was undertaken with the primary objective of evaluating the feasibility of a raga listening intervention for blood pressure among the Malaysian Indian population. This exploratory study was a single-centered randomized controlled trial consisting of fifty participants. The treatment group was required to listen to raga music daily, twice a day for thirty minutes per session for two weeks. The control group continued their daily activities and was only requested not to listen to raga music. Blood pressure was measured at the start and end of the two-week intervention period. The Depression, Anxiety and Stress Scale-21 was used to evaluate mood parameters. All participants in the treatment group complied and adhered to the required intervention. There was no statistically significant difference in systolic, diastolic blood pressure and heart rate between the treatment and control groups (p-values of 0.822, 0.937 and 0.861). A statistically significant decline in blood pressure was observed within the treatment group (-11.48 mmHg for systolic, -5.61 mmHg for diastolic blood pressure), but not in the control group. There was a significant decrease in stress scores in the treatment group with a p-value of 0.027 at post-intervention compared to the control group. Within the treatment group, there was a significant decrease in depression, anxiety, and stress scores (p-value